2012
DOI: 10.1186/1472-6831-12-4
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' perceptions of the aesthetic impact of dental fluorosis vs. other dental conditions in areas with and without water fluoridation

Abstract: BackgroundThe use of fluorides for caries prevention is well established but is linked with an increased risk of dental fluorosis, some of which may be considered to be aesthetically objectionable. Patient opinion should be considered when determining impact on aesthetics. The aim of this study was to assess participant rating of dental aesthetics (from photographic images) of 11 to 13 year olds participating in an epidemiological caries and fluorosis survey in a fluoridated and a non-fluoridated community in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…These findings were different from Kershaw et al, McGrady et al and Browne et al, in which tooth color was associated with the poorest esthetic rating, as these studies did not include missing anterior teeth in their assessment criteria. [8][9][10] It is commonly thought that women were more concerned over their orofacial esthetic and more critical in judging their dental appearance [11]. In this study, both women and men expressed similar levels of satisfaction towards their orofacial esthetic.…”
Section: Discussionmentioning
confidence: 57%
“…These findings were different from Kershaw et al, McGrady et al and Browne et al, in which tooth color was associated with the poorest esthetic rating, as these studies did not include missing anterior teeth in their assessment criteria. [8][9][10] It is commonly thought that women were more concerned over their orofacial esthetic and more critical in judging their dental appearance [11]. In this study, both women and men expressed similar levels of satisfaction towards their orofacial esthetic.…”
Section: Discussionmentioning
confidence: 57%
“…The imaging method ensured the blinding of the examiner to participant exposure to water fluoridation, this technique has been tested and calibrated with successful results and has become well established through utilization in other research studies . Using images dictated that only incisors were used for scoring; this was considered acceptable because on an aesthetic level, these are the teeth that are most important …”
Section: Discussionmentioning
confidence: 99%
“…Many studies report the effects of fluorosis to be purely aesthetic, and that minor presentations of fluorosis are not of great concern to those affected . The links between fluorosis and psychosocial factors are limited; for example, Chankanka et al reported that at mild and moderate levels of fluorosis, there were no negative effects on oral health‐related quality of life in countries with community water fluoridation (USA, UK, Canada and Australia).…”
Section: Introductionmentioning
confidence: 99%
“…[143] In a recent study, adolescents answered a questionnaire regarding the impact of enamel fluorosis on dental aesthetics, older adolescents rated photographs of mild fluorosis more favorably than younger ones. A fluorosis score indicative of moderate fluorosis was the level considered to have aesthetic significance.…”
Section: Fluorosis Of Aesthetic Concernmentioning
confidence: 99%